Academic Hardiness and Active Procrastination: Levels and Correlation among University Students - Abu Bakar; Fajriani Fajriani; M. Husen; Nurrizki Shafira (ENLIGHTEN: Jurnal Bimbingan Konseling Islam, 2022)
Academic hardiness is a personality characteristic that can resist all academic pressures on students, while active procrastination is an activity or behavior that procrastinates intentionally, and repeatedly in completing academic tasks. The research objectives: (1) measure the level of active procrastination and academic hardiness of students, and (2) predict the relationship between academic hardiness and procrastination in students. The research uses a quantitative approach with the type of correlational research. The research population is active undergraduate students in one of the State Universities in Banda Aceh. Determination of the number of samples using the Slovin formula, from a population of 22,798 students obtained a sample of 393 students. The Clustered Random Sampling technique was used in the selection of samples with batch as the cluster from the 2016 to the 2020 batch. The data collection technique used a questionnaire contains two scales; namely Revised Academic Hardiness Scale (RAHS) and Active Procrastination Scale (APS). The results showed that the average active procrastination level was in the medium category, with a percentage of 68.4% and the average academic hardiness level was in the medium category with a percentage of 67.4%. Research shows that there is a significant positive relationship between academic hardiness and active procrastination with a Pearson correlation of 0.308 and a probability value of 0.000 (ρ <0.05). The results of this study can be used as the basis for making a hardiness trainer program by the University Counseling Service Unit to increase academic hardiness in students so that they can fight all academic pressures.